Analysis of Inflation, Regional Gross Domestic Product and Minimum Wage on Employment Absorption in East Nusa Tenggara Province - Rahmatullah, Muhammad Zidan Al Aziz; Marseto, Marseto (Journal of Business Management and Economic Development, 2024)
Based on observations of phenomena in the East Nusa Tenggara Province, this region demonstrates significant progress across various sectors such as tourism, education, and industry, supported by increases in minimum wages, constant domestic economic growth (constant GDRP), and relatively low inflation rates. However, this situation has not successfully optimized labor absorption. This study aims to examine the "Impact of Inflation, GDRP, and Minimum Wage on Employment Absorption in the East Nusa Tenggara Province". The methodology employed is multiple linear regression with a time range from 2010 to 2022, focusing on the East Nusa Tenggara Province. The independent variables in this study are inflation, GDRP, and minimum wage, while the dependent variable is employment absorption. The results indicate that inflation and minimum wage variables significantly influence employment absorption, while the GDRP variable does not affect employment absorption.